Edge of winter [videorecording (DVD)] - Connolly, Rob, 1982-; Kinnaman, Joel, 1979-; White, Percy Hynes; Sutherland, Rossif, 1978- (Sony Pictures Home Entertainment, 2016)
Brothers Brad and Caleb Baker embark on an outdoor bonding trip with their distant, somewhat unpredictable father Elliot. When they become stranded by a winter storm, the boys begin to suspect that it is their supposed protector who poses a larger threat than the elements.